Algumas interrogações acerca das produções midiáticas sobre a juventude - FRANCO, Ana Carolina Farias (Universidade Federal do Pará, 2017)
This article discusses the emergence of young and how the media has been cut by forging this disciplinary practices, rooted in the Standards development and how the deviations of the same. The notion of young, idealizes as one who is constituted as a creative, dynamic, rebellious and productive, healthy and a potential consumer of digital Technologies flexible can promote social mobilization of community. That the policies created for the Brazilian youth are focused on the axis of violence prevention and education to work. Although we discuss the vision of the Young elite linked to consumption and lifestyle associated with brands, to Sport and the use of digital devices.